Assessing Mutual Intelligibility between Kurmanji and Zazaki Spoken in Elâzığ at Text Level - Sağlam, Bilgit; Özek, Fatih; Buran, Ahmet; Gooskens, Charlotte (Dilbilim Dernegi, 2025)
This study examines the mutual intelligibility between Kurmanji and Zazaki. The research area selected for this study is the province of Elâzığ, where both languages are spoken. Participants consist of middle and high school students aged between 14–19 from nine district centers where Kurmanji or Zazaki is spoken as native language. The study included a total of 243 participants, with 27 individuals selected from each district. The participants' intelligibility levels of the test language were assessed through text-based tests designed at the B1 proficiency level. The study measured participants' perceived intelligibility of the test language by asking how much they understood and examined extralinguistic factors that might influence mutual intelligibility. In this context, the participants’ exposure to the test language and their attitudes toward it were assessed using a Likert scale. The findings indicate that mutual intelligibility between Kurmanji and Zazaki remains below 40% for both languages. Furthermore, no significant difference was found between participants' attitudes toward the test language and their functional test results. However, a significant correlation was identified between exposure to the test language and functional test scores. © 2025 Dilbilim Derneği, Ankara.
Elâzığ’da Konuşulan Kurmançça ve Zazaca Arasında Metin Düzeyindeki Karşılıklı Anlaşılabilirlik
Keywords: Kurmanji; mutual intelligibility; recorded text testing; Zazaki